Combined use of Quantiferon and HBHA-based IGRA supports tuberculosis diagnosis and therapy management in children. Issue 6 (December 2018) - Sali, Michela; Buonsenso, Danilo; D'Alfonso, Pamela; De Maio, Flavio; Ceccarelli, Manuela; Battah, Basem; Palucci, Ivana; Chiacchio, Teresa; Goletti, Delia; Sanguinetti, Maurizio; Valentini, Piero; Delogu, Giovanni
Summary: Objectives: Interferon- γ release assays (IGRA) are designed for diagnosis of tuberculosis (TB) infection, and do not discriminate latent TB infection (LTBI) from active TB. Heparin-binding hemagglutinin antigen (HBHA) emerged as a promising antigen for TB diagnosis when used in IGRA format. Aim of this study was to prospectively evaluate the performance of an HBHA-based IGRA to support TB diagnosis and TB therapy monitoring in children with TB infection or active TB disease. Methods: Following clinical, microbiological and radiological assessment, children (0–14 years old) were tested by the QuantiFERON TB-Gold In tube (QFT) assay and an aliquot of whole-blood was stimulated with HBHA and IFNγ evaluated only in QFT-positive subjects. Results: Among the 550 children tested, 486 (88.4%) scored negative and 64 (11.6%) positive. None of the QFT-negative had active TB. Among the QFT-positive, 45 were with LTBI and 19 active TB. HBHA-IGRA scored positive in 41/45 children (91.1%) with LTBI and in 6/19 active TB children (31.6%) at diagnosis ( p = 0.001); remarkably, 5 of these 6 children with active TB scoring HBHA-positive were asymptomatic. Moreover, following TB-specific therapy, most of the non-HBHA-responding children, gained an HBHA-positive response. Conclusions: HBHA-based IGRA is a useful support in TB diagnosis and TB-therapy monitoring in children.